T-Stability of the Heun Method and Balanced Method for Solving Stochastic Differential Delay Equations - Xiaolin Zhu; Hu Peng (Journal of Applied Mathematics)
This paper studies the T-stability of the Heun method and balanced method for solving stochastic differential delay equations (SDDEs). Two T-stable conditions of the Heun method are obtained for two kinds of linear SDDEs. Moreover, two conditions under which the balanced method is T-stable are obtained for two kinds of linear SDDEs. Some numerical examples verify the theoretical results proposed.